Pengetahuan Lokal Masyarakat Kepulauan Tentang Tumbuhan Anti-nyamuk - Said Hasan; Dharmawaty M Taher; M. Nasir Tamalene (TECHNO: JURNAL PENELITIAN, 2020)
The Utilization of natural materials from local plants as mosquito repellent starts from the deepening of information about local knowledge of the community. Research about anti-mosquito is important to overcome problems of the use of synthetic anti-mosquitoes on the market; besides that, this is also to preserve the community's local wisdom. The purpose of this study is to describe the local knowledge of the island community about the use of anti-mosquito plants and analyze the potential of plants that are most widely used by people in the islands as anti-mosquito lotion products. The method used is the exploratory survey method. Data collection is done by interviewing techniques, in-depth observation of informants, and documentation. The most used anti-mosquito plant data were analyzed by phytochemical components. The results showed that there were 9 species of anti-mosquito plants used by the community, namely Tagetes erecta L, Lavandula L, Cymbopogon citratus, Citrus aurantifolia, Syzygium aromaticum, Evodia suaveolens, Catharanthus roseus (L) G. Don., Alphitonia incana BL., and Polygala paniculata. Alphitonia incana BL is the most widely used type of society and contains phytochemical compounds, alkaloids, terpenoids, flavonoids, phenolics, and tannins. The Alphitonia incana BL., has the potential to be developed as an anti-mosquito lotion product.